Bringing it 'Home'? Sociological Practice and the Practice of Sociology. (October 2016) - Meer, Nasar; Leonard, Pauline; Taylor, Steve; O'Connor, Henrietta; Offer, John
Since Sociology was established in 1967, the journal has assumed a significant role in shaping the discipline. In the interim years it is often said that the very practice of sociology has now 'spun out' beyond the dedicated departments that were once the centres of sociological practice . This raises questions as to the relationship between sociology and other disciplines, questions that are compelling and arguably distinct from a welcome recognition of sociology's undoubted intellectual hybridity. The extent to which this is a productive tension or one that requires a resolution is an ongoing conversation to which this special issue speaks. In this introductory article we take what we consider to be an innovative route that is guided by the theme of 'Bringing Sociology Home' whilst simultaneously recognising the enormous strengths brought by the multidisciplinary developments of the last 50 volumes. We set out the terrain before introducing a mixture of short and substantive papers from contributors, as well as interviews, with scholars who have made a contribution to the study of the discipline of sociology both inside and beyond the pages of the journal.